Front Cover: Internal Donors in Ziegler–Natta Systems: is Reduction by AlR3 a Requirement for Donor Clean‐Up? (ChemCatChem 5/2018). Issue 5 (8th March 2018) - Zaccaria, Francesco; Vittoria, Antonio; Correa, Andrea; Ehm, Christian; Budzelaar, Peter H. M.; Busico, Vincenzo; Cipullo, Roberta
Abstract : The Front Cover shows the reaction deck of a glove‐box‐contained robotic platform used to investigate the chemisorption of Al‐alkyls and organic donors on the surface of MgCl2 ‐supported Ziegler–Natta catalysts for the industrial production of isotactic polypropylene. In this complex catalysis, Al‐alkyls are used to alkylate and reduce the inherently chiral but sterically open surface Ti precursor species; and one or more organic donors co‐adsorbed at neighboring surface locations impart the necessary steric hindrance to the active sites, thus mimicking ancillary ligands in molecular catalysts. In their Full Paper, F. Zaccaria et al. elucidate the different routes and mechanisms that can be exploited to steer this delicate operation of surface modification.